Haematological and biochemical alterations in native sheep experimentally infected with bluetongue virus serotype-2 - KHORAJIYA, J H; SINGH, K P; BHATT, PANKAJ; SAMINATHAN, M; TIWARI, S; BHAT, S A; VINEETHA, S; MAITY, M; PANDA, SHIBANI; GUPTA, V K (The Indian Journal of Animal Sciences, 2019)
The study was designed to determine the haematological and biochemical alterations in sero-negative native sheep following the experimental bluetongue virus serotype-2 (BTV-2) infection. The BTV infected group comprised 14 sheep inoculated with 6 ml of clarified virus containing 1Ã—106/ml TCID50 of BTV-2 by intradermal route. The uninfected control group comprised 6 animals inoculated with 6 ml of cell culture medium without virus by intradermal route. The blood and serum samples were analyzed at 0, 1, 2, 3, 7, 11, 14, 21 and 45 days post-infection (dpi). Significant changes were observed in all the haematological and biochemical parameters studied. Marked leucopenia was observed from 2 to 7 dpi in BTV infected group. Significant leucocytosis was documented during 11 to 14 dpi in infected group. Significant thrombocytopenia was observed during 2 to 14 dpi whereas significantly low packed cell volume (PCV) and haemoglobin (Hb) values were observed between 3 and 21 dpi in BTV infected group. Differential leucocyte count revealed significantly low lymphocyte percentage on day 3 and high on day 11 in infected group. The various biochemical enzymes like alanine aminotransferase (ALT) showed significantlyhigh values during 3 to 21 dpi, aspartate aminotransferase (AST) during 3 to 21 dpi, alkaline phosphatise (ALP) during 3 to 11 dpi and creatine kinase (CK) during 7 to 14 dpi in BTV infected group. The result of our study demonstrated significantly decreased levels of total leucocyte count, total platelet count, haemoglobin and PCV values while significantly increased levels of ALT, AST, ALP and CK values in BTV infected group. On histopathological examination, spleen and lymph nodes showed depletion of lymphoid cells, liver and kidney showed degeneration, congestion and haemorrhage at many places. The BTV nucleic acid was detected from blood and tissues by RT-PCR. These findings indicated the damage to various soft tissue organs and muscles as a sequel to vascular endothelial damages caused by BTV.